2013
DOI: 10.1186/1423-0127-20-100
|View full text |Cite
|
Sign up to set email alerts
|

Over-expression of microRNA-494 up-regulates hypoxia-inducible factor-1 alpha expression via PI3K/Akt pathway and protects against hypoxia-induced apoptosis

Abstract: BackgroundHypoxia-inducible factor-1 alpha (HIF-1α) is one of the key regulators of hypoxia/ischemia. MicroRNA-494 (miR-494) had cardioprotective effects against ischemia/reperfusion (I/R)-induced injury, but its functional relationship with HIF-1α was unknown. This study was undertaken to determine if miR-494 was involved in the induction of HIF-1α.ResultsQuantitative RT-PCR showed that miR-494 was up-regulated to peak after 4 hours of hypoxia in human liver cell line L02. To investigate the role of miR-494, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
47
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 34 publications
0
47
0
Order By: Relevance
“…Some studies show that miR-125a-5p prompted the activation and proliferation of hepatic stellate cell by partially down-regulating FIH1 in liver fibrosis [15], and miR-133a-5p was protective against hypoxia/reoxygenation (H/R) injury in vitro by targeting MAPK6 in hepatocytes [56]. Moreover, miR-146a could ameliorate liver hypoxia/reoxygenation injury in vitro by directly suppressing IRAK1 and TRAF6 [12] and miR-494 was protective against hypoxia-induced apoptosis in liver through HIF-1α upregulation by activating PI3K/ Akt pathway [14]. In addition, there is accumulating evidence suggesting that many other miRNAs are involved in liver reactions to hypoxic stress, such as miR-150 downregulation under hypoxia by targeting VEGF-A and HIF1α during liver regeneration [16, 57], miR-192-5p upregulation in hepatocyte injury [13] and increased miR-462/731 cluster in the hypoxia-exposed liver of Megalobrama amblycephala [58] and zebrafish [59].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies show that miR-125a-5p prompted the activation and proliferation of hepatic stellate cell by partially down-regulating FIH1 in liver fibrosis [15], and miR-133a-5p was protective against hypoxia/reoxygenation (H/R) injury in vitro by targeting MAPK6 in hepatocytes [56]. Moreover, miR-146a could ameliorate liver hypoxia/reoxygenation injury in vitro by directly suppressing IRAK1 and TRAF6 [12] and miR-494 was protective against hypoxia-induced apoptosis in liver through HIF-1α upregulation by activating PI3K/ Akt pathway [14]. In addition, there is accumulating evidence suggesting that many other miRNAs are involved in liver reactions to hypoxic stress, such as miR-150 downregulation under hypoxia by targeting VEGF-A and HIF1α during liver regeneration [16, 57], miR-192-5p upregulation in hepatocyte injury [13] and increased miR-462/731 cluster in the hypoxia-exposed liver of Megalobrama amblycephala [58] and zebrafish [59].…”
Section: Discussionmentioning
confidence: 99%
“…For example, miR-146a attenuates hypoxia/reoxygenation injury in vitro by directly suppressing IRAK1 and TRAF6 in liver [12] and miR-192-5p protects liver cell from hepatic injury induced by oxidative stress by targeting Zeb2 [13]. Also, miR-494 protects against hypoxia-induced apoptosis by upregulating HIF1α expression through activating PI3K/Akt pathway [14]. Moreover, miR-125a-5p prompts the activation and proliferation of hepatic stellate cells by targeting FIH1 [15], while miR-150 is involved in liver regeneration by targeting VEGF-A [16].…”
Section: Introductionmentioning
confidence: 99%
“…Nine in vitro cell culture studies were reported using various cell lines. Oxygen concentrations for in vitro hypoxia were set as 1% in 7 studies [14,[21][22][23][24]40,41], 0% in one study [8], and 1% or 0.1% in one study [25]. In animal hypoxia models, oxygen concentration was varied from 0% to 21% (asphyxia, hypoxia, and normoxia) with time spans from acute hypoxia to tolerant hypoxia.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…24) And overexpression of microRNA-494 upregulates HIF-1α expression via PI3 K/Akt pathway and protects against hypoxia-induced apoptosis. 25) microRNA-210 is widely induced by hypoxia in various types of cells, such as cardiomyocytes, 26) keratinocyte 27) , and other cells. microRNA-210 has been indicated to exert neuroprotective effects against oxygen-glucose deprivation through apoptosis inhibition in PC12 cells, 28) and to induce angiogenesis and neurogenesis in the normal adult mouse brain.…”
mentioning
confidence: 99%